2012
DOI: 10.1080/13825585.2011.633160
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of prospective memory through a familiarization intervention in old adults

Abstract: Younger adults consistently outperform older adults in laboratory prospective memory tasks. This study examines the effectiveness of an intervention that familiarizes older adults with the sequence of ongoing events to compensate their reduced prospective memory performance. We compared performance and electrophysiological measures of an intervention group (N = 20, 69-83 years) receiving a familiarization intervention to an individually matched control group (N = 20). As ongoing activity a 2-back working memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…A number of assessment tools have been developed to diagnose, assess, and evaluate the effects of different treatments on PM. Laboratory PM tasks (e.g., lexical decision task in Ihle et al, 2018 ; two-back working memory task in Zöllig et al, 2012 ) and naturalistic PM tasks (e.g., telephone call task in Troyer, 2001 ; writing the day of the week in Burkard et al, 2014b ) are commonly used to measure PM performance in older adults. Validated objective PM assessments (e.g., the Cambridge Test of Prospective Memory [CAMPROMPT]; Wilson et al, 2005 ) and self-reported questionnaires (e.g., Prospective and Retrospective Memory Questionnaire [PRMQ]; Crawford et al, 2003 ; Comprehensive Assessment of Prospective Memory [CAPM]; Chau et al, 2007 ) are also used to diagnose and evaluate PM impairment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A number of assessment tools have been developed to diagnose, assess, and evaluate the effects of different treatments on PM. Laboratory PM tasks (e.g., lexical decision task in Ihle et al, 2018 ; two-back working memory task in Zöllig et al, 2012 ) and naturalistic PM tasks (e.g., telephone call task in Troyer, 2001 ; writing the day of the week in Burkard et al, 2014b ) are commonly used to measure PM performance in older adults. Validated objective PM assessments (e.g., the Cambridge Test of Prospective Memory [CAMPROMPT]; Wilson et al, 2005 ) and self-reported questionnaires (e.g., Prospective and Retrospective Memory Questionnaire [PRMQ]; Crawford et al, 2003 ; Comprehensive Assessment of Prospective Memory [CAPM]; Chau et al, 2007 ) are also used to diagnose and evaluate PM impairment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…EEG electrodes) were averaged according to the outlined topographical clusters depicted in Fig. 3 (Appendix 2), which were informed through previous PM ERP research [16,30,45,46]. Averaging the connection weights of the input neurons offers a way of understanding differences in local connection weight changes between the groups within a specific area.…”
Section: Knowledge Extraction From Snn Modelsmentioning
confidence: 99%
“…However, the functional approach to development is equally applicable to the dynamic recruitment of neural structures to achieve stability in more complex outcomes (e.g., Imfeld, Oechslin, Meyer, Loenneker, & Jäncke, 2009; Münte, Altenmüller, & Jäncke, 2002). In this context, consider that, as individuals age, they may have to recruit neural networks differently to achieve the same performance outcome (e.g., Bezzola, Mérillat, & Jäncke, 2012; Hayes & Cabeza, 2008; Willis, Schaie, & Martin, 2009; Zöllig, Mattli, Sutter, Aurelio, & Martin, 2012). The approach may also be applied on the levels of genetics, cells, organs, individuals, and societies.…”
Section: An Example Application Of a Functional Approach: The Fqol Modelmentioning
confidence: 99%